THE ARGENTINE PRESIDENTIAL SYSTEM: BASIS FOR INSTITUTIONAL INNOVATION IN THE 21ST CENTURY. (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
In the present work, we will see the debate between the parliamentary and presidential system in the institutional design of Argentina, the general characteristics of each one of them and the advantages and disadvantages presented by presidentialism, according to the opinions of different specialists. We will mention the yearnings and objectives of the 1994 constitutional convention and the practical results obtained in the constitutional reform, with emphasis on the figure of the Chief of Cabinet and the legislative powers granted to the Executive Branch. After evaluating the Argentine institutional design, and the different opinions and variants proposed by the doctrine, we will make a brief conclusion on this.
Keywords: presidentialism; parliamentarism; executive branch; legislative branch; democracy